Anatomy and Physiology of Right Heart Adaptation to Pulmonary Arterial Hypertension Along with Treatment - Najma Attaullah, Mahvish Javed, Mariya Azam Khattak, Malik Shandar Khan, Sahar Farhat, Tanveer Tara, Sudhair Abbas Bangash, Farwa Daar, Umar Amin Malhi, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Right ventricular (RV) performance is directly correlated with staying alive in individuals with the pulmonary arterial hypertension (PAH). There is still large degree of heterogeneity in the RV’s response to pulmonary hypertension, despite the fact that the load of pulmonary i.e. lung, is a key factor in determining RV systolic performance in PAH. Objective: The main reason why this study was conducted to find out the normal differential function, interrelationships, and response to pulmonary arterial hypertension apical, right ventricular (RV) input and outflow compartments (PAH). Methods:40 individuals were examined using echocardiography which was 2-dimensional (2D) and also 3-dimensional (3D) in addition to traditional Doppler methods, including 15 controls, with the number of patients with left-sided heart failure was 25, 13 without secondary PAH which was named group-1 (G1) and 12 with secondary PAH was calledgroup-2 (G2). Results: The apical ejection percent was lower in controls than in patients for example the ejection of control was p≤0.01 and p≤0.01, for G1 it was: p≤0.05 and p≤0.01 and the ejection fraction forG2 was: p≤0.05 and p≤0.01, as well as in patients. The Inflow was decreased i.e.: p≤0.001 for both, same in the case of the apical: p≤0.01 for both, and again also in outflow tract: p≤0.05 for both patients showed decreased ejection percent. In G2, however, the inflow compartment achieved the minimal volume simultaneously with the outflow and apex, as opposed to controls where it took 20 ms for it to do so. In patients (in G1: the apical ejection percent was p=0.02 and p=0.01 and forG2 it was: p=0.01 for both), the times for both isovolumic contraction and that of relaxation were lengthened. In controls, volumetric outflow rate decline and the peak RV ejection time were associated (r=0.6, p0.05), however G2’s peak RV ejection time was connected with the apex. Conclusion: The inflow of the right side ventricular, apical, and also the outflow tract compartments each have distinctive characteristics and share to the total combined systolic function to varying degrees. The ventricle of the right side becomes one non synchronous compartment in PAH, that can lead to a long-term impact on systemic cardiac dysfunction.